The Use of YouTube Media in Increasing Motivation for Students in the Distance Learning Period - Nuzul Hidayat; Ahmad Arif; Muslim Muslim; M. Yasep Setiawan; Riwayatul Ismi (AEEJ : Journal of Automotive Engineering and Vocational Education, 2024)
The purpose of this study is to provide assistance to students in understanding the material presented by the teacher during the period during course. The method applied in this research is descriptive qualitative method. The population group studied were students taking the Automotive Simulation and computing course in the odd semester of the 2021/2022 academic year, who were enrolled in the Automotive Engineering Education study program at the Faculty of Engineering, UNP. The results of the study show that the use of video media in the form of course via YouTube makes a positive contribution to the course process and understanding of the material for students. The responses from students to the use of video as a course tool for Simulation and Computing showed that 85.66% of them responded well, while 14.34% responded at a poor level. The results of the study show that 50.8% of students have a "good" rating, 8.73% get an "very good" assessment, and 40.47% are in the "enough" category.